Neuraxial block for delivery among women with low platelet counts: a retrospective analysis. (August 2018) - Levy, N.; Goren, O.; Cattan, A.; Weiniger, C.F.; Matot, I.
Highlights: Women with low platelet counts may be excluded from a neuraxial block for delivery. General anesthesia rates are higher among women with low platelet counts. Data on 308 neuraxial blocks among women with a platelet count <100 000/μL. There were no cases of spinal epidural hematoma. The risk of a neuraxial hematoma when platelet count is <70 000/μL remains unknown. Abstract: Background: Laboring women with low platelet counts may be denied neuraxial block due to concerns about causing a spinal-epidural hematoma. Aims: To assess the anesthetic management, complications and outcome variables of women with low platelet counts, and to expand the existing data regarding the safety of neuraxial blocks in this patient population. Methods: This is a retrospective analysis of anesthetic and obstetric data from women with platelet counts <100 000/μL, who were admitted to a single referral center during 2011–2014. The rate of neuraxial block and related complications were examined in relation to the platelet count and the results combined with published data to assess the risk of spinal-epidural hematoma. Results: During the study period, 471 of 45 462 women (1%) had a low platelet count (<100 000/μL). The rate of neuraxial block was significantly higher in women with platelet counts of 70–99 000/μL (280/394, 71.1%) when compared to women with platelet counts of 50–69 000/μL and 0 to 49 000/μL (23/59, 38.9% and 5/18, 27.8%, respectively, P  <0.0001). Women in the lower platelet count ranges had a higher risk of cesarean delivery under general anesthesia and longer hospital stay. No neuraxial hematoma were reported. Conclusions: This study contributes a substantial series of neuraxial blocks among women with low platelet counts. The findings support that the risk of hematoma is low if the platelet count is <100 000/μL, specifically between 70 and 99 000/μL. Risk assessment in the lower count ranges requires a much larger sample.